Kajian Sistematis Mekanisme Kegagalan Struktural Wire Rope pada Sistem Crane Industri dan Efektivitas Metode Inspeksi Non-Destructive Testing (NDT) - Arraffi, Femas; Priyana, Onny Andre; Jasmine, Khulud Nur; Putri, Talita Andina; Purnama, Satria Candra; Priyanto, Kaleb (SURYA TEKNIKA, 2026)
Wire rope is a critical component in industrial crane systems, susceptible to structural failure due to cyclic loading, fretting wear, and corrosion. Prior reviews have addressed failure mechanisms or Non-Destructive Testing (NDT) methods in isolation, without integrating both perspectives or incorporating Indonesian national literature. This study systematically analyzes wire rope structural failure mechanisms and comparatively evaluates the effectiveness of various NDT methods through a Systematic Literature Review (SLR) following the PRISMA protocol. Searches across Scopus, ScienceDirect, Google Scholar, and Portal Garuda (2002–2025) identified 159 articles, of which 35 met the inclusion criteria. Literature quality was assessed using an adapted CASP/NOS rubric, yielding a mean score of 7.2/10. Findings indicate that fatigue induced by fretting wear is the most frequently reported failure mode (84% of studies), with Von Mises stress concentrations at strand-sheave contact points consistently exceeding the yield strength of wire steel (≈650 MPa). Among NDT methods evaluated, Magnetic Flux Leakage (MFL) demonstrated the highest relative performance, with defect classification accuracy reaching 95.3% and a minimum detectable metallic area loss of 1–2% under laboratory conditions. Synthesis of findings yields a conceptual framework for NDT- and condition-based maintenance (CBM)-integrated wire rope integrity management as the principal contribution of this study.